Novel 3, 4-dihydro-1, 4-oxazine (dehydromorpholine) sulfonamides and sulfones conveniently accessed from suitable a-diazoketones via OH carbene insertion – Cyclization sequence. (17th August 2021) - Solovyev, Igor; Dar'in, Dmitry; Krasavin, Mikhail
Graphical abstract: Highlights: Morpholines with novel substitution patterns are sought after in drug design. α-Acyl-α-diazomethane sulfon(amid)es are ameanable by the SAFE method. These have been coupled with 2-bromoethanol via Rh(II)-catalyzed reaction. The intermediates were transformed into dehydromorpholines. The process involves tandem S N 2/enamine formation (in this or reverse order). Abstract: A short and practically convenient, modular approach to hitherto unknown dehydromorpholine sulfones and sulfonamides from α-acyl-α-diazomethyl sulfones and sulfonamides, respectively, has been developed. It involves Rh(II) carbene insertion into the OH bond of 2-bromoethanol followed by thermally promoted tandem S N 2 displacement of the bromine atom by a primary amine and cyclodehydration.